The Relationship Between Role Overload and Work Stress in Nurses at Muhammadiyah General Hospital Bandung, Tulungagung District - Anik Nuridayanti; Nurhidayah; Jajuk Winarni (Kirana Publisher (KNPub), 2022)
Nurses are health workers who play a very important role in health services. Therefore the workload of a nurse is very heavy. A nurse who has to carry out her duties for the patient's recovery, on the other hand, the nurse's own psychological state must be maintained. These conditions can cause feelings of depression and stress in nurses. The heavier the workload of a nurse, the higher the level of work stress. The type of research used is correlational analytic with cross sectional approach. The population of 58 respondents and a sample of 50 respondents using purposive sampling technique. The independent variable is role overload and the dependent variable is work stress. Collecting data using a questionnaire and analyzed using the Spearman rank test with a significance of p <0.05.The results showed that most of the respondents had a heavy workload as many as 36 respondents (72%). Most of the respondents had moderate stress as many as 27 respondents (54%). Based on the Spearman test, it is known that the significance value or Sig. (2-tailed) of 0.000, because the value of Sig. (2-tailed) 0.000 < less than p=0.05, it means that there is a significant relationship between workload and work stress. It was concluded that there was a relationship between role overload and work stress on nurses at Muhammadiyah General Hospital Bandung Tulungagung . It is recommended for further researchers to look at the workload not only from the patient aspect, but also other aspects such as the level of expertise of nurses, organizational aspects and the work environment of nurses in order to obtain a more comprehensive picture of the workload of nurses.